Hadronization properties in e+e- annihilation at S=0 60GeV centre of mass energy - Zomorrodian, M.E.; Hasheminia, M.; Mirjalili, A. (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The hadronic events from the experimental data , as well as the PYTHIA Monte-carlo data at the 60 GeV centre of mass energies are studied.We present the general properties of multihadron final states produced by e+e- .Globalshape, inclusive charged-particle, and particle-flow distributions are presented. Our measurements are comparedwith QCD + fragmentation models that use either leading-logarithmic parton-shower evolution or QCD matrixelements at the parton level, and either string or cluster fragmentation for hadronization. Possible explanations forourcompariaon are presented in this paper.